2013
DOI: 10.1007/s11552-013-9559-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographic Factors and Comorbidities on Distal Radius Fracture Outcomes

Abstract: Background Despite the prevalence and consequences of distal radius fracture (DRF), there is limited research that analyzes the effects of demographic factors and comorbidities as they relate to pain, perceived disability, and functional outcomes. Methods All data for this study were examined retrospectively within an established clinical database. Patients with DRF were evaluated during their first and final visits with a criterion-based numeric pain scale (CR12), the Disability of the Arm, Shoulder, and Hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A few studies with short-term follow-up (6 or 12 months) reported that sex/gender has no influence on pain and disability experienced after DRF treated either operatively or nonoperatively. 18,64,78,79 In contrast, recent studies reported that women had higher levels of residual pain, 75 disability, 68 and poor function 80 among patients with postoperative DRF such that elderly women had greater disability compared with elderly men; however, quality of life did not differ. 68 Similarly, there is lack of consensus around the role of sex/gender on mortality rates after DRF.…”
Section: Risk Factorsmentioning
confidence: 87%
“…A few studies with short-term follow-up (6 or 12 months) reported that sex/gender has no influence on pain and disability experienced after DRF treated either operatively or nonoperatively. 18,64,78,79 In contrast, recent studies reported that women had higher levels of residual pain, 75 disability, 68 and poor function 80 among patients with postoperative DRF such that elderly women had greater disability compared with elderly men; however, quality of life did not differ. 68 Similarly, there is lack of consensus around the role of sex/gender on mortality rates after DRF.…”
Section: Risk Factorsmentioning
confidence: 87%
“…Many DRF patients experience noteworthy pain and disability during recovery, particularly those patients with multiple comorbidities, and post-acute care could ease recovery. (37) For many conditions, post-acute care is one of the largest contributors of variation in Medicare payments to hospitals around episodes of surgery care and one of the fastest growing categories of healthcare expenditures. (38) Furthermore, bundled payment and shared savings programs are directed to provide stronger incentives to improve recovery from common, acute conditions in a cost-efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of days between injury and initial therapy evaluation were inversely correlated with changes in perceived pain and disability as measured by the criterionbased numeric pain scale (CR12) and DASH questionnaire (r = −0.315 and −0.348, respectively; P = .000 for both). 36 A prospective study found that injury compensation was the most influential predictor of pain and disability at 1 year (P = .006) 10 and that those who completed postsecondary training had lower PRWE and DASH scores than those who did not (P = .016). 10 Worker's compensation has also been found to be strongly associated with pain (visual analog scale [VAS] score; regression coefficient, 3.1; 95% CI, 2.15-4.1) and function (regression coefficient = 16.5; 95% CI, 8.7-24.3) in a retrospective review of DRF patients.…”
Section: Occupation/employment Status/othermentioning
confidence: 99%